Bilateral agreement for the period 2007/2010 Socrates programme: higher education Erasmus between Universidade Lusíada de Lisboa and Universidade Católica San Antonio de Murcia - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities within the Socrates programme. - Subject area: Economics.